ANALISIS PENGARUH KUALITAS LAYANAN INTI DAN KUALITAS LAYANAN PERIPHERAL TERHADAP KEPUASAN PELANGGAN UNTUK MENCIPTAKAN MINAT WORDS OF MOUTH YANG POSITIF PADA COMMERCIAL BANKING CENTER JAWA TENGAH PT. BANK MANDIRI (PERSERO) TBK - Jelita, Ronarata Novarina (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2013)
This research is done based on phenomena that occured because of research result differences (research gap) about customer satisfaction and positive words of mouth in marketing. Besides, there are also research problem about customer satisfaction that decrease in banking industy, impacting number of customers decrease too, so that company in banking industry must improving their service quality to increase customers satisfaction. The impact from good customers satisfaction will give a positive effects in a way to increase positive words of mouth recording with the aim to increase number of customers.Some condition and factor above were importance to be checked empirically and analyzed. Therefore the practitioner/managerial in banking industry can obtain facts to support them in making decision and good strategy for their company. This research is done by taking research object at one of business unit in PT. Bank Mandiri (Persero) Tbk, Commercial Banking Center Jawa Tengah, amounting to 164 customers within. With the number of 164 customers, very possibles to do a sensus to all of the customers, so that all of the customers become a respondense. Analysis technique that used to interpret and analyze data in this research is technique of Structural Equation Model (SEM) of software package AMOS.Result examination proven hypothesis that factors core service quality and peripheral service quality become positive effect of customers satisfaction, and futhermore customers satisfaction become positive effect of positive words of mouth. It is mean high significance of each other variables. As for model which is raised in this research can be accepted posed at by index according of TLI 0,983 and value of CFI 0,986, all have up to standard, although of AGFI 0,897 accepted by marginal.